2005
DOI: 10.2337/diabetes.54.10.2988
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase IV Inhibition for the Treatment of Type 2 Diabetes

Abstract: Dipeptidyl peptidase (DPP)-IV inhibitors are a new approach to the treatment of type 2 diabetes. DPP-IV is a member of a family of serine peptidases that includes quiescent cell proline dipeptidase (QPP), DPP8, and DPP9; DPP-IV is a key regulator of incretin hormones, but the functions of other family members are unknown. To determine the importance of selective DPP-IV inhibition for the treatment of diabetes, we tested selective inhibitors of DPP-IV, DPP8/DPP9, or QPP in 2-week rat toxicity studies and in acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
314
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 488 publications
(327 citation statements)
references
References 31 publications
9
314
0
3
Order By: Relevance
“…DP8 expression upregulation by activated T cells and T cell proliferation suppression by DP8/9 inhibitors suggests that such substrates and thus a role of DP8/9 may be in immune cells [32,37]. The present study showed that thiol groups of DP8 and DP9 are targets of oxidation -reduction processes that impact upon enzyme activity.…”
Section: Discussionsupporting
confidence: 50%
“…DP8 expression upregulation by activated T cells and T cell proliferation suppression by DP8/9 inhibitors suggests that such substrates and thus a role of DP8/9 may be in immune cells [32,37]. The present study showed that thiol groups of DP8 and DP9 are targets of oxidation -reduction processes that impact upon enzyme activity.…”
Section: Discussionsupporting
confidence: 50%
“…Although the DPPIV inhibitor Ile-thia has been shown to also inhibit the intracellularly located DPPIV-related dipeptidyl peptidases DP8 and DP9, the results obtained from the DPPIV neg rats and the in vitro experiments with CCL11 and serum give strong evidence that the observed effects virtually depend on the activity of DPPIV (36).…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were observed in female animals w(-/-) 1.88"0.1 mU/mL; (q/q) 36.1"1.2 mU/mL; (q/-) 15.3"0.9 mU/mLx. In support of DP4 being the key regulator in glucose homeostasis, testing glucose tolerance in the OGTT revealed a significantly improved response towards glucose load in DP4 deficient rats wF(2,20)s10.04, ps0.001; Figure 1Bx, being comparable to pharmacologically induced DP4 deficiency in mice (29,30). Interestingly, heterozygous animals exhibited an intermediate phenotype, clearly illustrating an association between ''gene dosis'', DP4 activity, and glucose tolerance.…”
Section: Dp4 Deficiency Reduces Body Weight Protects From High-fat Dmentioning
confidence: 71%